Diketopyrrolopyrrole-based small molecules for solution-processed n-channel organic thin film transistors. Issue 44 (30th October 2019) - Zhou, Qian; Jiang, Yu; Du, Tian; Wang, Zhongli; Liang, Ziqi; Han, Yang; Deng, Yunfeng; Tian, Hongkun; Geng, Yanhou
Abstract : n-Type small molecules exhibit a highly reliable mobility of up to 1.05 cm 2 V −1 s −1 in solution-processed organic thin film transistors. Abstract : Four conjugated molecules with thiophene-flanked diketopyrrolopyrrole (DPP) as the core and 3-(dicyanomethylidene)indan-1-one (IC), dichlorinated IC (2Cl-IC) and difluorinated IC (2F-IC) as termini, i.e. DPP1012, DPP1012-4Cl, DPP1012-4F and DPP68-4F were synthesized. These molecules have similar band gaps of ca. 1.2 eV and deep lowest unoccupied molecular orbital (LUMO) energy levels below −4.1 eV. Single crystal structure analysis showed that DPP68-4F adopted a slipped one dimensional π-stacking structure with a π–π stacking distance of 3.57 Å in crystals. Top gate/bottom contact (TG/BC) organic thin film transistors (OTFTs) were fabricated via spin-coating. All molecules exhibited typical n-type characteristics with an electron mobility ( μ e ) of up to 0.44, 0.26, 1.05 and 0.58 cm 2 V −1 s −1 for DPP1012, DPP1012-4Cl, DPP1012-4F and DPP68-4F, respectively. Devices based on DPP1012-4F displayed the best device performance since its films were characterized by the highest packing order and appropriate film morphology. This work shows the great potential of the integration of the planar conjugated core and IC-type termini in designing solution processable high mobility n-type small molecule semiconductors.